UPAYA MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN PEMAHAMAN KONSEP MELALUI MODEL KOOPERATIF LEARNING TIPE THINK PAIR SHARE (TPS) DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMP N 11 KOTA BENGKULU - NOVIANITA, LIZZA; Susanta, Agus; fachruddin, fachruddin (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
This research is classroom action research (PTK) with data collection technique through activity observation sheet and test result of student learning. The subjects of this study are the students of class VII A SMP Negeri 11 Kota Bengkulu Odd Semester of the School Year 2017 which amounted to 32 students. The results showed that the implementation of learning strategy through cooperative model of learning type Think Pair Share (TPS) can increase student learning activity and learning outcomes. The increase of student learning activity can be seen from the value of observation of student learning activity of mathematics cycle I that is 19,67 (criteria enough), cycle II is 23,17 (good criterion), cycle III 26,17 (good criterion). Improvement of students' mathematics learning outcomes can be seen from the average score of student learning outcomes cycle I is 67.40; cycle II is 75,47; and cycle III has increase that is 82,34 and completeness of classical learning cycle I, cycle II, cycle III in sequence is 44%, 50%, and 81,25%. Keywords: Activities, Learning Outcomes, cooperative learning type Think Pair Share (TPS).